Theoretical model for seawater and sea sand concrete-filled circular FRP tubular stub columns under axial compression. (1st April 2018) - Li, Y.L.; Teng, J.G.; Zhao, X.L.; Singh Raman, R.K.
Highlights: FRP tubes filled with seawater and sea sand concrete (SWSSC) is studied. A theoretical model for SWSSC-filled FRP tubes in compression is proposed. The orthotropic behaviour of FRP tubes is properly accounted for in the model. A simplified method is proposed to determine the load shared by the FRP tube. The interaction between the FRP tube and the SWSSC is explicitly modelled. Abstract: The use of FRP with seawater and sea sand concrete (SWSSC) holds great potential for marine and coastal infrastructure, and concrete-filled FRP tubular columns are among the attractive forms of structural members for such applications. This paper presents a theoretical model for the compressive behaviour of seawater and sea sand concrete-filled circular FRP tubular stub columns. FRP tubes can be manufactured to possess considerable strength and stiffness in the longitudinal direction, so the behaviour of concrete-filled FRP tubes differed substantially from that of concrete columns with an FRP wrap (also referred to as "concrete-filled FRP wraps") which commonly contains fibres only in the hoop direction. Many theoretical models have been proposed for concrete-filled FRP wraps, but very limited work has been conducted on the theoretical modelling of concrete-filled FRP tubes. In the present study, an existing dilation model for concrete-filled FRP wraps is combined with a biaxial stress analysis of the FRP tube so that the effect of the Poisson's ratio of the FRP tube is properly accounted for. In order to predict the buckling of the FRP tube, a maximum strain buckling failure criterion is proposed and is shown to be in reasonable agreement with the experimental results. Moreover, the load carried by the FRP tube is studied, and a simplified model is proposed to determine the load shared by the FRP tube during the entire loading process. Finally, a theoretical model for SWSSC-filled FRP tubular columns is proposed, in which the behaviour of both the concrete and the FRP tube as well as their interactions are explicitly modelled (i.e., an analysis-oriented model). The proposed model gives reasonably close predictions of the existing experimental data.